Topological studies of molecular interactions of 1,4-dioxane with formamides or anilines at 308.15 K - Kumar S.; Maken A.; Agarwal S.; Maken S. (My University, 2025)
Molar excess volumes have been measured for 1,4-dioxane (A) + formamide, or N,N-dimethylformamide, aniline, N,N-dimethylaniline (B) mixtures at 308.15 K. For an equimolar A + B mixture, molar excess volumes follow the sequence: aniline < formamide < N,N-dimethylformamide < N,N-dimethylaniline. The excess volume data have also been rationalized by graph-theoretical arguments. This analysis has further yielded information about the state of association in aniline, formamide and N,N-dimethylformamide that is consistent with the existing views on their nature of association. The existence of molecular entities in these mixtures has also been supported by their infrared spectral studies. © 2010 Elsevier B.V. All rights reserved.